Harvard of the East - Ishak, Mohamed Mustafa (The Star, 2014)
THE campus community at Universiti Utara Malaysia is known largely to thrive on its research and inpovation.As the only management university in Malaysia, we are eager to make ourselves known as the "Harvard of the East".